Toward a Model of Cognitive Insight in First-Episode Psychosis: Verbal Memory and Hippocampal Structure - Buchy, L. (Oxford University Press, 2010)
Our previous work has linked verbal learning and memory with cognitive insight, but not clinical insight, in individuals with a first-episode psychosis (FEP). The current study reassessed the neurocognitive basis of cognitive and clinical insight and explored their neural basis in 61 FEP patients. Cognitive insight was measured with the Beck Cognitive Insight Scale (BCIS) and clinical insight with the Scale to assess Unawareness of Mental Disorder (SUMD). Global measures for 7 domains of cognition were examined. Hippocampi were manually segmented in to 3 parts: the body, head, and tail. Verbal learning and memory significantly correlated with the BCIS composite index. Composite index scores were significantly associated with total left hippocampal (HC) volume; partial correlations, however, revealed that this relationship was attributable largely to verbal memory performance. The BCIS self-certainty subscale significantly and inversely correlated with bilateral HC volumes, and these associations were independent of verbal learning and memory performance. The BCIS self-reflectiveness subscale significantly correlated with verbal learning and memory but not with HC volume. No significant correlations emerged between the SUMD and verbal memory or HC volume. These results strengthen our previous assertion that in individuals with an FEP cognitive insight may rely on memory whereby current experiences are appraised based on previous ones. The HC may be a viable location among others for the brain system that underlies aspects of cognitive insight in individuals with an FEP.